Iskanje informacij po horizontalno porazdeljenih virih - Pohorec, Sandi (Uporabna informatika (Ljubljana), 2009)
In the modern society the use of online search engines is a daily routine. More often than not it is the only way of getting the desired information instantly. For a large web portal, with the ambition to provide their users with advanced search services, the feature specifications of the search services they require far exceed the capabilities provided by large search engines (Google, Yahoo, Live Search). The main initiative for a custom search service is the need for security and authorized access to certain content; also the desired personalization level and a customized ranking of search results are both major contributors. The paper reviews the architecture of modern search engines and presents in greater detail the search service that was developed. The service provides automated use of users'' credentials to limit the search results to only the content that the user has been granted access to, it provides centralized search capability across multiple web siteswith similar content as well as structured and unstructured data sources.The search service also provides personalization according to the user''s field of interest.
Keywords: internet; semantični splet; spletni iskalniki; spletni portali; iskanje informacij; iskalni indeksi; spletni pajki; porazdeljeni viri